Strengthening Presidential Institutions in Indonesia: A Policy Analysis for Governance Reform - Mukhlis, Muhammad Mutawalli; Lohalo, Georges Olemanu; Balebo, Piaget Mpoto; ImÅ¡iroviÄ‡, Mirela (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
This study examines the urgency of strengthening Indonesia's presidential institution to enhance governance and adapt to contemporary challenges. The research aims to assess the institution's capacity to ensure political stability, promote democratic values, and address corruption and centralization of power. Utilizing mixed methods, the study combines surveys, in-depth interviews, and direct observation, supported by thematic and statistical analysis. Key findings indicate that improving inter-institutional collaboration, adopting innovative decision-making strategies, and leveraging technology for transparency are crucial for addressing governance challenges. The study concludes that reforms in legal frameworks and accountability mechanisms are vital for enhancing public trust and institutional responsiveness. These findings provide actionable insights for policymakers to advance democratic governance and institutional resilience